The implications of ambitious decarbonisation of heat and road transport for Britain's net zero carbon energy systems. (1st January 2022) - Chaudry, Modassar; Jayasuriya, Lahiru; Blainey, Simon; Lovric, Milan; Hall, Jim W.; Russell, Tom; Jenkins, Nick; Wu, Jianzhong
Highlights: A novel integrated energy and transport system modelling approach is described. A combination of heat and transport decarbonisation options are assessed. Managed EV charging and vehicle to grid reduces energy system (opex + capex) costs. Hydrogen technologies for heating and transport are costly to implement. An integrated energy system enables increased utilisation of renewable energy. Abstract: Decarbonisation of heating and road transport are regarded as necessary but very challenging steps on the pathway to net zero carbon emissions. Assessing the most efficient routes to decarbonise these sectors requires an integrated view of energy and road transport systems. Here we describe how a national gas and electricity transmission network model was extended to represent multiple local energy systems and coupled with a national energy demand and road transport model. The integrated models were applied to assess a range of technologies and policies for heating and transport where the UK's 2050 net zero carbon emissions target is met. Overall, annual primary energy use is projected to reduce by between 25% and 50% by 2050 compared to 2015, due to ambitious efficiency improvements within homes and vehicles. However, both annual and peak electricity demands in 2050 are more than double compared with 2015. Managed electric vehicle charging could save 14TWh/year in gas-fired power generation at peak times, and associated emissions, whilst vehicle-to-grid services could provide 10GW of electricity supply during peak hours. Together, managed vehicle charging, and vehicle-to-grid supplies could result in a 16% reduction in total annual energy costs. The provision of fast public charging facilities could reduce peak electricity demand by 17GW and save an estimated £650 million annually. Although using hydrogen for heating and transport spreads the hydrogen network costs between homeowners and motorists, it is still estimated to be more costly overall compared to an all-electric scenario. Bio-energy electricity generation plants with carbon capture and storage are required to drive overall energy system emissions to net zero, utilisation of which is lowest when heating is electrified, and road transport consists of a mix of electric and hydrogen fuel-cell vehicles. The analysis demonstrates the need for an integrated systems approach to energy and transport policies and for coordination between national and local governments.